Features of the rational use of innovation and investment clusters of construction enterprises under the conditions of business relocation to overcome the crisis of marital state in Ukraine - Lavrukhina, K. (Ways to Improve Construction Efficiency, 2023)
The main condition for innovative development of the country is the innovative potential of the construction industry, as the flagship of today's urban reconstruction. This article is devoted to the characteristics of the innovative potential of the country's construction industry, in particular, the main innovative problems of the Ukrainian economy are analyzed and recommendations are made for their improvement. The organization and stimulation of processes of technology renewal, the transfer of scientific developments from the field of knowledge acquisition to production, which is achieved with the help of the development of the education system, the intellectual property market, the creation of innovative infrastructure, financial and tax stimulation of scientific and technical activities, is of particular importance in the processes of the functioning of the national innovation system. etc. Thus, the situation in the innovation sphere makes it urgent to develop such a state policy that would ensure expanded reproduction of the object base of innovative activity and the irreversible impact of innovations on accelerated economic growth of the country. The relevance is due to forced changes in the regional socio-economic policy of Ukraine due to the relocation of property and enterprises from areas of risk and active hostilities. The economic front of the state during the war is one of the issues, ensuring the activity of which contributes to replenishing the budget and maintaining the solvency of the population. The improvement of the efficiency and transparency of the work of city authorities and services was analyzed, namely: integration and coordination of individual functions and city services to optimize the solution of complex problems and speed up interdepartmental interaction; improvement of the system of control over the activity of communal enterprises and budget organizations; improvement of the statistical information collection system to improve the efficiency of management decision-making on the ground; ensuring effective management of city assets.